Studying The Problem of Future Arabic Language Teacher Competence as A Socio-Pedagogical Necessity (Eurasian Journal of Learning and Academic Teaching, 2023)
The article discusses the issues of creating conditions for students studying in higher educational institutions to acquire a wide range of opportunities for them to obtain modern knowledge in conditions that meet international standards, the issue of teaching Arabic in an unconventional style is also becoming relevant at the present time, human capital is needed to master foreign languages, which is the competence of a future Arabic teacher language, degree, position what is the reason for the underdevelopment, the formation of the competence of the future teacher of the Arabic language